Children and professionals rights to participation: a case study - Mesquita, Cristina (2014)
This study investigates the process of praxiological transformation developed in an early childhood education institution, in Portugal, within four activity rooms. It is a single case study using action research, context-based staff development and participatory childhood pedagogy as means to change educational practices. It undertakes thorough dialogues with the Childhood Association pedagogical approach for children learning and teachers’ development, as well as with Effective Early Learning Project as reference for monitoring and evaluating quality co-construction. This has been a long and complex process that has had positive effects in the transformation of practices (staff development) and on children learning and participation. The reconceptualization of the image of the child has been a key for their right to participate and a professional motivation for educators to change practices.